When mothers talk about their past habits: A case study of stunting in Kendary City, Indonesia - Lisnawaty Lisnawaty; Meynanda Meynanda; Fithria Fithria; Irma Yunawati; Febriana Muchtar (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2020)
Stunting can be a nutritional problem that will adversely affect the optimal development process of children according to their genetic potential. Stunting can hinder the process of growth and development in under-fives. This study aimed to determine the causes of stunting in under-fives in the Abeli sub-district, Kendari City. The method of study was descriptive qualitative by a case study design. Data obtained through in-depth interviews of 4 (four) key informants and 5 (five) ordinary informants. Based on the results of the study, it was known that the incidence of stunting in the Abeli sub-district was caused by low birth weight, exclusive breastfeeding, and complementary feeding. It was based on the results of interviews, of four under-fives were stunting, there were three under-fives had a birth weight <2500 grams. The reason was because of inadequate breast milk production and a lack of family support for mothers to provide exclusive breastfeeding to under-fives. The reason was that the mother did not carry out routine pregnancy checks so that the condition of the fetus was poorly monitored. Besides, all under-fives who were stunting did not receive exclusive breastfeeding. In giving complementary feeding, the mothers gave complementary feeding to under-fives too early. Besides, a portion of the meal did not meet the needs of under-fives and less varied food.